Health Technologies for preventing physical disabilities caused by leprosy - Candido, Stephany Costa Novo; Almeida, Priscilla Dantas (Revista Prevenção de Infecção e Saúde, 2023)
Introduction: Leprosy is of significant public health concern as it is an infectious and chronic disease with the potential to cause physical disabilities. Aim: To identify health technologies in scientific literature for preventing physical disabilities caused by leprosy. Outlining: This is an integrative literature review, based on the research question: "What health technologies are applied to prevent physical disabilities caused by leprosy?" formulated using the PICo strategy, where "P" stands for Population (leprosy), "I" for phenomenon of Interest (technologies), and "Co" for Context of the study (prevention of physical disabilities). Results: Eleven articles published between 2001 and 2020 in Brazil were included. More than seventy technologies were identified for use in disability prevention. The primary types of health technologies for preventing physical disabilities include strategies and materials such as lectures, home visits, and establishing a strong relationship between healthcare professionals and patients. Implications: It was identified that in the context of preventing physical disabilities caused by leprosy, assistive technology (assessment of physical disabilities, wound care, and immobilization, among others); educational technology (such as guidance on hygiene and proper medication use); and managerial technology (clinical meetings, for example) play crucial roles.